Legenden der Jeremia-Exegese (II): Die Verschleppung Jeremias nach Ägypten - Stipp, Hermann-Josef (Vetus Testamentum, 2014)
The article examines the widely accepted theory that according to Jer 43:5-7 Jeremiah was forced to emigrate to Egypt by his fellow-countrymen. The scrutiny concludes that the assumption, besides being inherently improbable, not only lacks a textual basis but contradicts important features of the source. Therefore, it ought to be abandoned.